De la quête spirituelle à la quête de légitimité : Samskara et enjeux de reconnaissance d’ascètes européens ou nord-américains en Inde - de Guise, Catherine (Anthropologica, 2023)
When the discussion turns to India, the exotic image of the Hindu ascetic fills the imagination of contemporary society. Becoming an ascetic implies living in isolation to devote oneself to spiritual attainment. For those who are Hindu by birth, asceticism positions itself, from the outset, as a path to choose to achieve ultimate deliverance and guarantee the preservation of the cosmic order. For people from secular, individualized and materialistic contexts, choosing asceticism is an autonomous and marginal choice, one that is distinct and even contrary to their social and religious obligations. However, some abandoned their cultural and religious heritage to don the saffron-coloured robe and adopt an ascetic lifestyle in a context where, traditionally, you do not become Hindu, you are born Hindu. By emphasizing the experience of their spirituality, the analysis shows that their construction of a spiritual self is subject to an unending process of both subjective and collective validation. Referring first to the concept of saṃskāra, the imprints left by previous lives, to justify and interpret their decisions, these ascetics then validate their ascetic practices through interactions with their peers via the definition of a self-recognition framework that is unique to them.